(untitled) (CIPEEX, 2025)
The present study aims to systematically analyze the main reasons that lead to digital exclusion or third-level digital divide, as well as their impacts on Society. Based on a literature review approach, research was conducted on databases such as Scopus, Web of Science, and SciELO, using inclusion criteria for articles published in English, with free access and full availability of articles, published between 2020 and 2024. As a strategy for the searches, three blocks of words related to the following terms were used: Digital Exclusion, Information Technologies, and Digital Divide The topic of digital exclusion was approached by studying socioeconomic, educational, geographical, and infrastructure factors After removing duplicate articles, opinions, comments, and case reports, the final analysis was based on 7 full articles, considering the methods used, relevance, and domain of the subject, as well as the main results identified. The data showed that digital exclusion refers to inequality in access, use, and effective study of information and communication technologies (TIC), consisting of a divide between individuals who have adequate access to TIC and those who do not, as well as the existing gap between them. The lack of internet access stands out as one of the main drivers of digital exclusion, being identified as a reinforcement of existing social inequalities in a digitized world Sociodemographic and socioeconomic factors often parallel the lack of access to these resources, highlighting that actions are frequently shaped by an individual’s social context Considerations regarding the effective security of digital means also play a role, generating some resentment among new users. Digital exclusion occurs due to various factors similar to societies, with the notable observation that individuals in situations of loneliness, poverty, lack of education, or precarious health are at a risk three to five times higher for digital exclusion compared to their counterparts. The study significantly contributes to the understanding of socioeconomic conditions among various groups in society and their access to TIC, as well as the existing gap between them It establishes a solid foundation for future research and prevention and correction practices related to technological exclusion, providing valuable insights that can guide subsequent developments in business strategies and relevant public policies.